Coaching knowledge, sport emotion, and perceived performance in Korean judoka - Nam, K. W.; Ha, J. H.; Yoon, S. J. (Frontiers in Psychology, 2025)
Introduction: Perceived performance is associated with coaches` expert knowledge and athletes` sport emotion; however, the relationships among these variables have not been studied. This study aimed to investigate the structural relationships between the coaching knowledge of judo coaches and the sport emotion and perceived performance of Korean judo practitioners, or "judoka."